The effectiveness of training and competency development of library staffs in improving the quality of work and motivation in the PTDI / Nurulakma Mohamed Bahkia - Mohamed Bahkia, Nurulakma (2014)
A questionnaire was used to collect data. The analysis of the data exposed high levels of the effectiveness of training programs in the Tun Dr. Ismail Library, UiTM Johor campus Segamat and to identify the satisfaction levels of library staffs about training programs among respondents. The respondents also showed a positive attitude towards the topic. Suggestions aimed at to improving the Tun Dr. Ismail Library, UiTM campus Johor (PT DI) training and competency development were also provided The purpose of this research is to study the effectiveness of training and development competency of library staffs in improving the quality of work and motivation in the Tun Dr. Ismail Library, UiTM Johor campus Segamat and to identify the satisfaction levels of library staffs about training programs. Questionnaire and interview methods were used for the study. A sample size of 28 library staff from the Tun Dr. Ismail Library, UiTM campus Johor (PT DI) was selected through simple random sampling.